2019
DOI: 10.3389/fmats.2019.00018
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Enhanced Adsorption of High-Density Polyelectrolyte Nucleation-Inducing Seed Layer for Highly Conductive Transparent Ultrathin Metal Films

Abstract: In recent years, ultrathin Ag films (UTAFs), which are attractive owing to its extremely low resistance, relatively high transparency, excellent mechanical flexibility, and mature mass production, have been reported as potential candidates to replace traditional indium tin oxide (ITO). To achieve a high-quality UTAF, a nucleation-inducing seed layer (NISL) is required to address the issue of irregular Ag islands growth. However, the structures of films so deposited are still far from being ideal and consist of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…It has been reported that the intensity of the chemical reaction can be quantified by the amount of shift of the binding energy peak of a gold atom (e.g., in the Au-4f region) revealed by X-ray photoelectron spectroscopy (XPS) for different PEM conditions. [25,26] From the XPS analysis of the 8 nm-thick gold deposited on various combinations of PEMs (see the details in Experimental Section), all of the combinations of PEMs led to a negative shift of the binding energy of Au-4f from the gold on bare substrate condition. Among all the combinations of PEMs, the Au/(PEI/ PSS) 5 condition resulted in the largest negative shift of the Au-4f binding energy (the XPS spectra in Figure 1c, the values of the negative shift of energy in Figure 1d).…”
Section: Optimization Of Ultrathin Gold Electrodes On Pem Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the intensity of the chemical reaction can be quantified by the amount of shift of the binding energy peak of a gold atom (e.g., in the Au-4f region) revealed by X-ray photoelectron spectroscopy (XPS) for different PEM conditions. [25,26] From the XPS analysis of the 8 nm-thick gold deposited on various combinations of PEMs (see the details in Experimental Section), all of the combinations of PEMs led to a negative shift of the binding energy of Au-4f from the gold on bare substrate condition. Among all the combinations of PEMs, the Au/(PEI/ PSS) 5 condition resulted in the largest negative shift of the Au-4f binding energy (the XPS spectra in Figure 1c, the values of the negative shift of energy in Figure 1d).…”
Section: Optimization Of Ultrathin Gold Electrodes On Pem Coatingmentioning
confidence: 99%
“…Recently, for optoelectronic devices such as photovoltaic cells and light-emitting diodes, it has been reported that vacuumdeposited ultrathin metal film (<10 nm), which is transparent but originally non-conductive, can become highly conductive when a certain type of polymer layer is used as the NISL. [25][26][27][28] The NISL prevents random migration and aggregation of evaporated metallic elements during vacuum deposition, and therefore improves electrical conductivity by reducing the grain boundaries. In this work, we adopted this approach to create transparent and flexible microelectrodes for efficient electro-optical neural interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…These seeds provide dense nucleation centers for metal deposition, and suppress the growth of large metal islands during the PVD process. Such functional seeding materials include metals (Al, [40][41][42] Au, [43] Ag, [44] and Cu [45] ), dielectrics (Ta 2 O 5 , [46] ZnO, [47][48][49] NiO, [50] TeO 2 , [51] Nb 2 O 5 , [52] MoO 3 , [53] and Cs 2 CO 3 [54] ), polymers (polyethyleneimine [PEI], [19,[55][56][57][58] Ormoclear, [59] and photoresist SU-8 [60] ), and organic monolayers (11-mercaptoundecanoic acid [MUA], [48] [3-aminopropyl]-trimethoxysilane: [3mercaptopropyl]-trimethoxysilane [APTMS:MPTMS], [42,61,62] methyl-terminated alucone, [63] and 1,4-bis[2-phenyl-1,10-phenanthrolin-4-yl]benzene [p-bPPhenB] [64] ). For example, Schubert et al enhanced the wetting of deposited Ag films by using high surface energy metal seed materials such as Ca, Al, and Au (Figure 2a).…”
Section: Introductionmentioning
confidence: 99%
“…[19] A branched polyethylenimine (PEI) layer is deposited on top of ZnO nanoparticles (NP) layer to reduce the granule size of ultra-thin Ag transparent electrode. [47][48][49] The resultant smooth ultra-thin Ag film effectively alleviates light scattering and improves the absorbing selectivity of ST-OPV. Further, with the guidance of optical simulation, an optical interference layer, that is, TeO 2 , is deposited on top of the ultra-thin Ag layer, and this dramatically improves absorbing selectivity via increasing the transmittance in visible region without significantly sacrificing absorption in invisible region.…”
Section: Introductionmentioning
confidence: 99%